2017
DOI: 10.1016/j.envint.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Health risks posed to infants in rural China by exposure to short- and medium-chain chlorinated paraffins in breast milk

Abstract: Chlorinated paraffins (CPs) are complex mixtures of synthetic chemicals found widely in environmental matrices. Short-chain CPs (SCCPs) are candidate persistent organic pollutants under the Stockholm Convention. There should be great concern about human exposure to SCCPs. Data on CP concentrations in human breast milk is scarce. This is the first study in which background SCCP and medium-chain CP (MCCP) body burdens in the general rural population of China have been estimated and health risks posed to nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 29 publications
(36 reference statements)
6
52
0
Order By: Relevance
“…Also, no significant differences could be observed between rural and urban areas in China. 107,108 The measured MCCP concentrations range between 3.10 and 240 ng/g lipid and are thus one order of magnitude lower than the SCCP concentrations measured in the same samples (with the exception of the concentrations measured in Germany 109 ) (Fig. 9).…”
Section: Mccp Concentrations In Mammalsmentioning
confidence: 67%
“…Also, no significant differences could be observed between rural and urban areas in China. 107,108 The measured MCCP concentrations range between 3.10 and 240 ng/g lipid and are thus one order of magnitude lower than the SCCP concentrations measured in the same samples (with the exception of the concentrations measured in Germany 109 ) (Fig. 9).…”
Section: Mccp Concentrations In Mammalsmentioning
confidence: 67%
“…Xia et al. ( 2017a ) reported SCCP and MCCP concentrations in pooled human milk samples from provinces and cities in China that, when summed in the samples with the lowest and highest SCCP and MCCP values, indicate total CP concentrations of lipid ( lipid). In contrast, the range of total CP concentrations in pooled samples from Asian countries in the present study was lipid ( lipid) ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…2012 ) indicated a clear dominance of SCCPs (e.g., United Kingdom 2006 median SCCP/MCCP ratio of 7.2). Two studies of samples collected from Chinese donors in 2007 and 2011 indicated a dominance of SCCPs over MCCPs by a factor of 10 ( Xia et al. 2017a , 2017b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors reported the concentrations of SCCPs and MCCPs in pooled human milk samples this time from rural areas from 24 Chinese provinces, for the same time frame 2007 and 2011 (Xia et al., 2017b). The levels were lower than those reported in the urban areas, with median SCCP and MCCP concentrations in 2007 of 303 and 35.7 ÎŒg/kg fat, respectively, and in 2011 of 360 and 45.4 ÎŒg/kg fat.…”
Section: Assessmentmentioning
confidence: 99%